NÅR HJEMME ER UDE: Betydningen og skabelsen af hjem i naturen blandt homesteadere i Oregon, USA - Jakobsen, Gry Skrædderdal (Tidsskriftet Antropologi, 2009)
Based on fi eldwork among homesteaders in the US Pacifi c Northwest, this article explores particular ways in which home is created and sustained in the light of the homesteaders’ ideals of becoming one with nature. The article focuses on how construction of houses is guided by such ideals and shows how the merging of home and nature is also taking place at a mundane level in social interaction. When building a house the homesteaders are seeking to discard standard urban ideas about which materials to use and how to furnish houses. In a long debate about how to deal with the fact that rats have entered the common kitchen, naturalisation and humanisation of both people and animals are employed in order to create a common ground. In sum the article argues that the homesteaders’ practises are serving both their effort to stand out from “mainstream” or “suburban” America as part of an ideological project to establish alternative ways of living, and that they also express a more existential struggle to create spaces of harmony and personal control in a modern world characterised by consumerism and globalisation. Keywords: Nature, U.S.A., alternative life styles, home.